(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A country looks for renaissance generally when its present is too much depleted and the future is even more uninspiring and bleak. This realization of being almost at the verge of extinction or nothingness as a culture, as a religion or as a nation does not come easily and smoothly.